Hemodialysis Patients: Factors Affecting Adherence to Treatment - Tri Hapsari Retno Agustiyowati; Ligar Widiani Sopia; Tri Antika Rizki Kusuma Putri (STIKep PPNI Jawa Barat, 2023)
Aims: Chronic kidney disease is a chronic and permanent kidney function decline characterized by a high glomerular filtration rate. Hemodialysis to treat chronic kidney disease is cleaning blood using a machine-assisted dialyzer carried out routinely. Aim: This study aims to determine the factors that influence therapy adherence in hemodialysis patients. Methods: This research is a quantitative study using a cross-sectional study design. This study used convenience sampling on 150 undergoing hemodialysis patients. The End Stage Renal Disease-Adherence Questionnaire (ESRD-AQ) was used to evaluate adherence. Independent variables were knowledge, social support, and motivation. Data analysis used Spearman correlation and logistic regression. Results: The results showed that the average age of the patients was 51.51, with most of them being male (57.3%). The results of the bivariate analysis showed that there was a relationship between social support and therapy adherence (p-value 0.017), there was a relationship between knowledge and therapy adherence (p-value 0.000), and there was a relationship between motivation and therapy adherence (p-value 0.018). The most influencing factor is motivation (p-value 0.002). Conclusion : The study found that knowledge, motivation, and social support significantly correlate with therapy adherence, with motivation being the most influencing factor. Nurses can improve awareness of adherence and use this as a reference for future research on CKD patients' hemodialysis therapy.